2019
DOI: 10.3846/mbmst.2019.137
|View full text |Cite
|
Sign up to set email alerts
|

The effect of glass powder on physical and mechanical properties of hardened cement paste

Abstract: The article analyses the effect of finely crushed glass on the properties of hardened cement paste. Materials used for the test: Portland cement CEM I 42.5 R, finely crushed glass (particle size ≤75 µm), and water. Seven compositions of cement paste mixes with different amounts of crushed glass (0%, 5%, 10%, 15%, 20%, 25%, 30%) added by weight of cement were designed. Compressive strength, density and ultrasonic pulse velocity of modified hardened cement paste with different content of crushed glass were measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Glass powder's impact on the characteristics of cement pastes that have hardened is tested by Barkauskas et al [9]. With constant types of cement and constant ratios of water to fines, seven compositions of cement paste mixes were used, each containing varying percentages of crushed glass (0-30%).…”
Section: Introductionmentioning
confidence: 99%
“…Glass powder's impact on the characteristics of cement pastes that have hardened is tested by Barkauskas et al [9]. With constant types of cement and constant ratios of water to fines, seven compositions of cement paste mixes were used, each containing varying percentages of crushed glass (0-30%).…”
Section: Introductionmentioning
confidence: 99%
“…Glass powder's impact on the characteristics of cement pastes that have hardened is tested by Barkauskas et al [25]. With constant types of cement and constant ratios of water to fines, seven compositions of cement paste mixes were used, each containing varying percentages of crushed glass (030%).…”
Section: Introductionmentioning
confidence: 99%
“…It was observed that the composite reinforced with 9 wt% coconut fiber showed the highest strength of modulus of rupture and compressive strength. Kstutis Barkauskas and al analyzed the effect of finely crushed glass on the properties of hardened cement paste (Kȩstutis et al 2019). The test results revealed that the hardened cement paste containing 5% ground glass by weight of cement was found to have higher strength and density than the unmodified cement paste.…”
Section: Introductionmentioning
confidence: 99%